Combining ability and heterosis analysis for yield traits in bread wheat (Triticum aestivum) - SINGH, VIKRANT; KRISHNA, RAM; SINGH, SANJAY; VIKRAM, PRASHANT (The Indian Journal of Agricultural Sciences, 2014)
In order to realize the combining ability and heterosis of wheat, 21 hybrids were synthesised in a 7 × 7 diallel fashion excluding reciprocals. Analyses of combining ability and heterosis over mid parent (MP) as well as economic parent (HD 2733) were undertaken for yield and its component traits. The experiment was conducted in 2007–08 and 2008–09 at Crop Research Farm of CSAUA &T, Kanpur, UP. The results revealed that non-additive genetic variance played a predominant role in the inheritance of most of the traits. The best combinations mostly involved high × low and low × low general combiners for the characters under study. There was very rare case in which high × high general combiners were involved for best combinations. On the basis of gca and sca effects, 3 parents (i e K 7903, K 9465 and HUW 234) and 14 cross combinations (i.e. 5 top crosses namely HD 2733 × K 7903, HUW 234 × K 9423, HD 2285 × K 2021, HUW 234 × K 2021 and K 9423 × K 2021) were found good general and specific combiners for higher grain yield and also for various yield contributing traits, respectively.